Henry & the Crazed Chicken Pirates - Crimi, Carolyn; Manders, John (Somerville, Mass. : Candlewick Press, 2009)
When the Buccaneer Bunnies receive a note from an unknown enemy, Henry researches and writes a book called "Plan for Impending Danger from the Unknown Enemy Who Wrote the Scary Note," which helps him when the enemy finally arrives.
Keywords: Rabbits -- Fiction; Books and reading -- Fiction; Authorship -- Fiction; Pirates -- Fiction; Chickens -- Fiction